Structurally confined ultrafine NiO nanoparticles on graphene as a highly efficient and durable electrode material for supercapacitors. Issue 56 (25th May 2016) - Cheng, Yi; Pan, Jian; Saunders, Martin; Yao, Shikui; Shen, Pei Kang; Wang, Huanting; Jiang, San Ping
Abstract : Core–shell structured ultrafine NiO NPs embedded in MnO x show high supercapacitance as well as excellent stability due to the structure confinement effect of amorphous MnO shell. Abstract : The most significant challenge in the development of ultrafine oxide based supercapacitors is the poor microstructure stability due to the rapid agglomeration of the fine nanoparticles (NPs). Here, we developed novel amorphous MnO x structurally confined ultrafine NiO NPs (∼2.3 nm) supported on graphene, NiO@MnO x via a simple and facile self-assembly process with the assistance of microwave sintering. NiO@MnO x with a NiO : MnO x weight ratio of 1 : 0.2 achieves a high capacitance of 966 F g −1 based on total electrode materials and 3222 F g −1 based on active materials at a discharge current density of 2 A g −1 . Remarkably, the materials retain 100% capacitance after 2000 cycles at a charge and discharge current of 10 A g −1 . In contrast, the durability of ultrafine NiO NPs without MnO x confinement is very poor, with 94% of the capacitance lost under identical cyclic conditions despite the initial high capacitance of 3696 F g −1 . The substantially enhanced capacitance, durability and high rate capacity contribute to the formation of a nanoporous and amorphous MnO x layer on ultrafine NiO NPs, which provides the extraordinary structural confinement and enhances the mass transfer process. The results provide a new strategy to develop highly efficient and durable ultrafine nanosized electrode materials for supercapacitors.